Design of prototype for the short circuit protection of DC bus using Arduino Uno and DSP controller - Giddalur, Eswaraiah; Laxmi, Askani Jaya (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Micro-grids (MGs) play a prominent role in the exchange of bulk power between loads and the central grid. MG can run in an islanding mode or grid-connected mode. When the central grid fails to provide power in such situations, MGs serves as power sources for critical facilities such as coordination facilities in railway stations and airports, transportation, university and research facilities. MGs use energy sources such as solar, wind, hydro, geothermal, and biomass to produce electricity along with rechargeable batteries, aircraft applications is continuously increasing. This leads to the development of DC MGs. A model of DC MG is located at the disaster management lab in the Department of Electrical and Electronics Engineering. The MG consists of step-downed and rectified DC power supply from conventional 230 V AC source, a PV array, wind, and a battery bank a source supplying power to a set of nine DC loads. Although DC MGs have many advantages compared to AC MGs, one of the challenges faced is the study of faults and protection of the DC MG. In this paper, a prototype for the existing system in the disaster management lab is designed in hardware and tested.